Emerging Roles of Disabled Homolog 2 (DAB2) in Immune Regulation - Figliuolo da Paz, Vanessa; Ghishan, Fayez K.; Kiela, Pawel R. (Frontiers in Immunology, 2020)
Disabled-2 (DAB2) is a clathrin and cargo binding endocytic adaptor protein recognized for its multifaceted roles in signaling pathways involved in cellular differentiation, proliferation, migration, tumor suppression, and other fundamental homeostatic cellular mechanisms. The requirement for DAB2 in the canonical TGFsignaling in fibroblasts suggested that a similar mechanism may exist in immune cells and that DAB2 may contribute to immunological tolerance and suppression of inflammatory responses. In this review, we synthesize the current state of knowledge on the roles of DAB2 in the cells of the innate and adaptive immune system, with particular focus on antigen presenting cells (APC; macrophages and dendritic cells) and regulatory T cells (Tregs). The emerging role of DAB2 in the immune system is that of an immunoregulatory molecule with significant roles in Treg-mediated immunosuppression, and suppression of TLR signaling in APC. DAB2 itself is downregulated by inflammatory stimuli, an event that likely contributes to the immunogenic function of APC. However, contrary findings have been described in neuroinflammatory disorders, thus suggesting a highly context-specific roles for DAB2 in immune cell regulation. There is need for better understanding of DAB2 regulation and its roles in different immune cells, their specialized sub-populations, and their responses under specific inflammatory conditions.